2020
DOI: 10.1136/bmjdrc-2020-001295
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Choroidal Vascularity Index of Haller’s layer in diabetic eyes precedes retinopathy

Abstract: IntroductionThe study aimed to evaluate Choroidal Vascularity Index (CVI) of Haller’s and Sattler’s layers and their relationships with choroidal and retinal thickness, volumes measured on enhanced depth imaging–optical coherence tomography (OCT) scans in the eyes of patients without diabetes, patients with diabetes with no diabetic retinopathy (DR) and patients with diabetes and DR.Research design and methodsRetrospective analysis of 165 eyes from 84 Singapore Indian Eye Study-2 study participants (group 1: n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 41 publications
(46 reference statements)
3
20
0
Order By: Relevance
“…When we further compared control mean values with our pooled DM group, LA, SA and TCA were significantly decreased in patients with DM, consistently with other studies [ 14 , 38 , 39 ]. Previous studies on the association between choroidal thickness and DR stage found a decreased thickness in patients with DM [ 12 , 14 ]. Interestingly, when we compared FChT between the NDR and DR groups, we found increased mean values in the DR group, 295.43 ± 86.83 µm vs. 269.51 ± 94.22 µm in NDR, although not statistically significant ( p = 0.332), as found by Xu et al and Tan et al [ 14 , 40 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…When we further compared control mean values with our pooled DM group, LA, SA and TCA were significantly decreased in patients with DM, consistently with other studies [ 14 , 38 , 39 ]. Previous studies on the association between choroidal thickness and DR stage found a decreased thickness in patients with DM [ 12 , 14 ]. Interestingly, when we compared FChT between the NDR and DR groups, we found increased mean values in the DR group, 295.43 ± 86.83 µm vs. 269.51 ± 94.22 µm in NDR, although not statistically significant ( p = 0.332), as found by Xu et al and Tan et al [ 14 , 40 ].…”
Section: Discussionmentioning
confidence: 98%
“…Ferrera et al have demonstrated a loss of intermediate and large vessels in Sattler’s and Haller’s layer in patients with DM [ 11 ]. Analysis of the choroidal vasculature anatomy showed that it is divided into small vessels that form the superficial choriocapillaris, medium-sized vessels consisting mainly of choroidal arterioles that form Sattler’s layer and deeper large vessels composed mostly of choroidal veins that form Haller’s layer [ 12 ]. It was observed that in eyes with diabetes but no DR, the choroidal vascularity index (CVI) decreases preferentially in larger choroidal veins (Haller’s layer) before medium-sized arterioles (Sattler’s layer) or smaller choriocapillaris, while the eyes with more than 5 years duration of diabetes had a lower macular CVI of Sattler’s layer when compared to the control group [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The small size of these groups, the different age, the higher variability of measurements or a true absence of difference may justify not reaching significance. Some previous studies have found a reduced CVI in DM patients without DR [ 25 27 ], while other have not [ 18 21 ]. It remains unclear if diabetic choroidopathy can be detected before classic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…First, our sample size was small and not evenly distributed among three different CAD severity groups. Although we performed multivariate analysis to reduce the confounding effects of the variables, there were significant differences in terms of underlying diseases such as diabetes and hypertension, among different groups which are known to be associated with a choroidal thickness or CVI values 20 22 . Second, although those in the no CAD group did not have significant coronary stenosis, there was no healthy control group without cardiovascular risk factors or symptoms.…”
Section: Discussionmentioning
confidence: 99%